Crystallographic details of the nucleotide-binding pocket of subunit A and B of A-ATP synthases and insight into the nucleotide-binding subunit α of the Escherichia coli F-ATP synthases - Vikeramjeet Singh Tadwal (2011)
Archaea are considered to be the most primitive organisms forming a separate evolutionary kingdom located near to the root of evolutionary tree, which have evolved separately during the course of evolution. Archaea have unique and efficient energy conserving mechanisms, which allow them to thrive under extreme eniornmental conditions. Archaeal A1AO ATP synthases (A-ATP synthases) are a separate class of energy converters, synthesizing adenosine triphosphate (ATP) by means of ion gradient-driven phosphorylation. These enzymes possess the unique capability to couple ATP synthesis to the transport of both, H+ and Na+ ions. An A-ATP synthase is composed of a total of nine types of subunits in the stoichiometry of A3:B3:C:D:E:F:H2:a:cx. Adenosine triphosphate is synthesized in the A1 domain of the A3B3 headpiece, and the energy provided for this process is transmitted to the membrane-bound AO domain. The energy coupling between the A3B3 hexamer and the AO sector occurs via the stalk subunits C, D and F. The sites for ATP synthesis or hydrolysis are located at the interfaces of A- and B-subunits, which are arranged alternately in hexameric fashion to form the A3B3 headpiece. A region that is critical for nucleotide binding in the A- and B-subunit of A-ATP synthases is the loop called as P-loop (phosphate-binding loop). The characteristic of the P-loop is the 8-amino acid consensus sequence GXXXGXGKT, which is conserved in several mononucleotide binding proteins including the A-subunit of A-ATP synthases.